Scientific Article: Problems in Investment Financing and Methods for Improving Their Resolution (Case of Uzbekistan) - Mirzaxojayeva Sayyora Shaxobidin qizi, (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2026)
This study examines the structural bottlenecks and systemic challenges in investment financing within the transition economy of Uzbekistan. Despite significant liberalization reforms since 2017, the reliance on public debt and state-guaranteed loans remains high, necessitating a shift toward private equity and capital market instruments.